A puzzle or mathematical problem? - Mačys, Juozas Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2016)
In the paper it is illustrated by some examples the difference between a mathematical problem, computer problem and puzzle. It is given detailed solution of the mathematical problem considered.
Keywords: puzzle; sudoku; kakuro; mathematical problem; computer problem